FIRST LANGUAGE ACQUISITION ON A THREE-YEAR-OLD CHILD - Yuliana Friska; Moh. Thoyib Syafi'i (Universitas Muhammadiyah Kalimantan Timur, 2021)
Studying children’s language acquisition is quite fascinating to be conducted because as we know that the astonishing advancement of their language obtaining from 0 to 3 years or more. The aim of the study is to obtain deep understanding about language acquisition on a three-year old child